ECO AERATOR: INOVASI PENYUPLAI OKSIGEN DENGAN TEKNOLOGI VERTICAL AXIS WIND DAN ARCHIMEDES SCREW GUNA MENURUNKAN BIAYA OPERASIONAL PETANI TAMBAK - Utama, Aditya Rifa; Mubarrok, Muhammad Fasih; A., Ardiansyah; Antomi, Hendra; Fathoni, Muhammad Januar; Dikairono, Rudy (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Acquirement oxygen supply to the pond ecosystem (aeration) is one of the essential needs for fish farmers. They mostly use diesel combined with a windmill as a tool for aeration (aerator). Operating and maintenance of diesel engine are big budget. Meanwhile value of renewable energy in the coastal area is very big such as the wind energy. It is also experienced by UD. Sumber Tani, Surabaya. There is a concept of Eco Aerator as renewably technological for innovation. That is the aerator with a simple concept using the vertical axis windmill technology and Archimedes screw to replacement diesel engine. Using vertical axis wind technology, the mill is able to rotate in any wind direction making it suitable to coastal areas that have the characteristics of the wind direction changing to move Archimedes screw. It is also have stability in rotational motion. The advantages of eco aerator is no need to have a continuous wind speed, because of its function as a supplier of dissolved oxygen into the water that does not have to constantly supply such as a generator of electricity, it is enough 10 hours a day like a pond aerator farmers. The application of this technology is very simple, easy to operate and low budget.